MATHEMATICAL MODELS FOR NUMERICAL ANALYSIS OF THE SCALING PROCESSES AT HEATING OF MOVING INGOTS - A. N. Chichko; A. S. Borozdin (Литьë и металлургия, 2004)
There is offered the mathematical model for numerical analysis of the processes of scaling, proceeding at heating of the moving ingot. There are carried out the computer calculations of the ingot heating in the furnaces with stage heating.